Relations between R&D Activities and Tax Allowances in Hungarian Car Trade Companies - Hustiné Béres , Klára; Tatár, Emese; Turzai-Horányi, Beatrix (Theory, Methodology, Practice – Review of Business and Management, 2014)
The research, development and innovation (R&D&I) activities of enterprises are highly influenced by the socio-economic environment. The product, process, and organizational innovations of enterprises can be stimulated both by direct and indirect tools. In this study, we listed all the R&D related tax allowances that are part of the corporate income tax regulation. By using primary data (including all Hungarian business associations), we analyzed how the car trading companies could utilize the available tax allowances. Our results showed how effective these tax allowances were in stimulating research and development activities. In our study, our main focus was to identify the reason for the low number of innovation activities.